2014
DOI: 10.2147/ijn.s51193
|View full text |Cite
|
Sign up to set email alerts
|

Novel interfaces for light directed neuronal stimulation: advances and challenges

Abstract: Light activation of neurons is a growing field with applications ranging from basic investigation of neuronal systems to the development of new therapeutic methods such as artificial retina. Many recent studies currently explore novel methods for optical stimulation with temporal and spatial precision. Novel materials in particular provide an opportunity to enhance contemporary approaches. Here we review recent advances towards light directed interfaces for neuronal stimulation, focusing on state-of-the-art na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 186 publications
(251 reference statements)
1
79
0
Order By: Relevance
“…It is reported that in certain scenarios, different organelles in the cells require light pulses of different wavelengths and exposures; therefore there is a need for systems with multispectral spatiotemporal optical switching capability152829. Figure 2(a) shows the ability of the probe to selectively illuminate multiple cells or cell regions with different wavelengths (488 nm and 561 nm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that in certain scenarios, different organelles in the cells require light pulses of different wavelengths and exposures; therefore there is a need for systems with multispectral spatiotemporal optical switching capability152829. Figure 2(a) shows the ability of the probe to selectively illuminate multiple cells or cell regions with different wavelengths (488 nm and 561 nm).…”
Section: Resultsmentioning
confidence: 99%
“…These targeted illumination based microscopes are either limited by spatial resolution, temporal resolution or both4. Though there are multi-photon based imaging systems available with high spatial and temporal resolution, they are of a conventional desktop type and not clinician-friendly probe imaging systems1516. Therefore designing a probe imaging system has incomparable advantage over other conventional microscopic systems.…”
mentioning
confidence: 99%
“…The Faradaic mechanism involves the transfer of an electron between the electrode and electrolyte (i.e., redox reaction), whereas the capacitive mechanism involves only charge redistribution near the electrode–electrolyte and/or electrolyte–cell membrane interfaces [27]. Given the fundamental differences in physical properties of various photoactive materials, there is no ‘generally applicable model’ for the interaction of these materials with cells [60]. …”
Section: Chemical Stimulationmentioning
confidence: 99%
“…Moreover, both light intensity and wavelength can be precisely regulated and thus diverse stimulation protocols can be applied. 3,4 However, the vast majority of animal cells do not present any specific sensitivity to light. Several strategies for optical stimulation have thus been proposed, either exploiting light-sensitive molecular mediators nearby or within the cells, or using photoactive device placed externally, close to the cell.…”
Section: Introductionmentioning
confidence: 99%